Pengaruh Pengembangan Karir terhadap Kinerja Karyawan dengan Kepuasan Kerja sebagai Variabel Intervening pada Bank Syariah Indonesia KCP Meulaboh Imam Bonjol - Debi Natila Rifa; Febyolla Presilawati; Husnaina Mailisa Safitri (Jurnal Sains dan Ilmu Terapan, 2026)
The purpose of this study was to determine and test the effect of career development on employee performance through job satisfaction at BSI KCP Meulaboh Imam Bonjol. The sample size of this study was 91 respondents. The research method was collected through a questionnaire and documentation study. Data processing was carried out using quantitative data analysis techniques. Statistical tools that can be used to test the functional relationship between dependent variables bound variables and independent variables free variables are path analysis at a 95 persen confidence level 0.05. The object of this study was at BSI KCP Meulaboh Imam Bonjol. The results showed that career development had an effect on employee performance at BSI KCP Meulaboh Imam Bonjol. Career development had an effect on Job Satisfaction at BSI KCP Meulaboh Imam Bonjol. Job satisfaction had an effect on employee performance at BSI KCP Meulaboh Imam Bonjol. Career development had an effect on Employee Performance at BSI KCP Meulaboh Imam Bonjol through Job Satisfaction as a mediating variable.